2023
DOI: 10.1212/wnl.0000000000206784
|View full text |Cite
|
Sign up to set email alerts
|

IV Thrombolysis Initiated Before Transfer for Endovascular Stroke Thrombectomy

Abstract: Background and objective:The role of intravenous thrombolysis (IVT) in patients with large vessel occlusions (LVOs)administered prior to transferfrom a primary stroke center (PCS) to a comprehensive stroke center (CSC) is questioned.Methods:We included observational studies of patients with an LVO receiving IVT at a PCS prior to their EVT transfer compared to those receiving EVT alone. Efficacy outcomes included excellent or good functional outcomes [modified Rankin Scale (mRS) scores of 0-1or0-2, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A recent meta-analysis of patients presenting to nonendovascular thrombectomy centers with large vessel occlusions showed that outcomes were better if rtPA was given prior to transfer to the endovascular center than if it was skipped. 46 Therefore, current practice is not to skip rtPA unless the patient presents directly to the endovascular thrombectomy center, has an endovascular suite; skin puncture occurred at 11:56 AM, and reperfusion with thrombolysis in cerebral infarction grade 3 flow was established at 12:26 PM. At 24 hours after symptom onset, the NIHSS score was 3 for mild right facial weakness, right arm pronator drift, and speech hesitancy.…”
Section: Case 2-2mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of patients presenting to nonendovascular thrombectomy centers with large vessel occlusions showed that outcomes were better if rtPA was given prior to transfer to the endovascular center than if it was skipped. 46 Therefore, current practice is not to skip rtPA unless the patient presents directly to the endovascular thrombectomy center, has an endovascular suite; skin puncture occurred at 11:56 AM, and reperfusion with thrombolysis in cerebral infarction grade 3 flow was established at 12:26 PM. At 24 hours after symptom onset, the NIHSS score was 3 for mild right facial weakness, right arm pronator drift, and speech hesitancy.…”
Section: Case 2-2mentioning
confidence: 99%
“…While rtPA is relatively ineffective in dissolving a large vessel occlusion, it can do so in 10% to 30% of cases, 45 particularly if administered in the first hour after last time known well and given 30 to 60 minutes to work. A recent meta-analysis of patients presenting to nonendovascular thrombectomy centers with large vessel occlusions showed that outcomes were better if rtPA was given prior to transfer to the endovascular center than if it was skipped 46 . Therefore, current practice is not to skip rtPA unless the patient presents directly to the endovascular thrombectomy center, has an approachable clot, and the thrombectomy team is immediately available.…”
Section: Interaction With Endovascular Thrombectomymentioning
confidence: 99%
“…The meta-analysis by Katsanos et al 5 provides further support for the current practice patterns in which patients who are eligible for IVT should have treatment initiated as soon as possible regardless of whether the patient is likely to be transferred for EVT. Based on the mixed results from the randomized trials of patients arriving initially at EVT-capable centers, there is also not compelling evidence to skip IVT for those patients not requiring transfer for EVT.…”
mentioning
confidence: 92%
“…3,4 There have not been any randomized trials that have included the large population of patients with LVO who arrive initially at a center without EVT capability and are subsequently transferred to an EVT-capable center for intervention. In this issue of Neurology ® , Katsanos et al 5 reported results of a systematic review and meta-analysis of observational studies investigating the question of utility and safety of IVT before transfer for EVT. The authors identified 6 studies with this patient population and performed a combined analysis that also included some primary patient data previously not published.…”
mentioning
confidence: 99%
“…These ‘slow progressor’ patients may constitute a third or more of transferred patients. While they can be identified with advanced imaging such as diffusion MRI and CT perfusion (CTP) [ 9 11 ], these resources are not often available at community hospitals and underserved regions [ 12 14 ]. This is especially true for patients in the extended window or with unknown onset [ 15 ].…”
Section: Introductionmentioning
confidence: 99%